Disaster risk analysis of technological failure of industrial estate: a case study: - Turniningtyas Ayu Rachmawati; Dwi Rahmawati (Universitas Serang Raya, 2023)
The world has agreed on reducing disaster risks through Sendai Framework for Disaster Risk Reduction (SFDRR) 2015–2030. Efforts to reduce disaster risks are one way to attain Sustainable Development Goals related to